Graphene quantum dots as a highly efficient solution-processed charge trapping medium for organic nano-floating gate memory. (24th February 2016) - Ji, Yongsung; Kim, Juhan; Cha, An-Na; Lee, Sang-A; Lee, Myung Woo; Suh, Jung Sang; Bae, Sukang; Moon, Byung Joon; Lee, Sang Hyun; Lee, Dong Su; Wang, Gunuk; Kim, Tae-Wook
Abstract: A highly efficient solution-processible charge trapping medium is a prerequisite to developing high-performance organic nano-floating gate memory (NFGM) devices. Although several candidates for the charge trapping layer have been proposed for organic memory, a method for significantly increasing the density of stored charges in nanoscale layers remains a considerable challenge. Here, solution-processible graphene quantum dots (GQDs) were prepared by a modified thermal plasma jet method; the GQDs were mostly composed of carbon without any serious oxidation, which was confirmed by x-ray photoelectron spectroscopy. These GQDs have multiple energy levels because of their size distribution, and they can be effectively utilized as charge trapping media for organic NFGM applications. The NFGM device exhibited excellent reversible switching characteristics, with an on/off current ratio greater than 10 6, a stable retention time of 10 4 s and reliable cycling endurance over 100 cycles. In particular, we estimated that the GQDs layer trapped ∼7.2 × 10 12 cm −2 charges per unit area, which is a much higher density than those of other solution-processible nanomaterials, suggesting that the GQDs layer holds promise as a highly efficient nanoscale charge trapping material.